A Comparison of Field Measures of Adiposity Among Australian Adolescents from the Raine Study - Chivers, P.; Hands, B.; Beilin, L.; Kendall, Garth; Bulsara, Max; Parker, H. (Universiti Teknologi MARA (UiTM), Malaysia, 2010)
This study examined the possible inter-changeability of common proxy measures of adiposity in adolescent 14 year olds from a large cohort. A sample of 1,607 adolescents (n = 825 male and n = 782 female) was drawn from the Western Australian Pregnancy Cohort (Raine) Study. Pearson Product Moment Correlation, Bland-Altman method, and Bland regression were used to determine the level of agreement between common proxy adiposity measures. The Bland-Altman and Bland regression results supported the notion that the two indices (Waist-height-Ratio and Body-Mass-Index) are measuring a similar construct (F = .974, p = .324). However 95 percent limits of agreement differed between the methods (95% CI [21.04, 21.52] and [17.71, 24.90] respectively), with the Bland regression approach suggesting that the measures are not interchangeable. These results provide evidence that different adiposity measures are not comparable, particularly when tracking weight status over time. The validity of WHR as an adiposity measure is questioned, and the similarity in weight status groupings based on WHtR and BMI, indicate these measures are most comparable.